First aid Q&A for the USMLE Step 2 CK - Tao Le (McGraw-Hill Medical Pub. Div., 2010)
Prepare to ace the USMLE Step 2 CK with First Aid Q&A for the USMLE Step 2 CK. The new second edition of this student-proven book features 1000 board-style questions along with easy to navigate, high-yield explanations of correct and incorrect answers. You'll also find hundreds of valuable images, diagrams, and tables. The book is correlated with First Aid for the USMLE Step 2 CK and First Aid Cases for the USMLE Step 2 CK for the ultimate review package!